Treatment of Caenorhabditis elegans with small selenium species enhances antioxidant defense systems - Rohn, Isabelle (Mol Nutr Food Res, 2019)
SCOPE: Small selenium (Se) species play a key role in Se metabolism and act as dietary sources of the essential trace element. However, they are redox active and trigger pro- and antioxidant responses. As health outcomes are strongly species-dependent, species-specific characteristics of Se compounds were tested in vivo. METHODS AND RESULTS: In the model organism Caenorhabditis elegans (C. elegans), immediate and sustained effects of selenite, selenomethionine (SeMet) and Se-methylselenocysteine (MeSeCys) were studied regarding their bioavailability, incorporation into proteins, as well as modulation of the cellular redox status. While all tested Se compounds were bioavailable, only SeMet persistently accumulated and was non-specifically incorporated into proteins. However, the protection towards chemically-induced formation of reactive species was independent of the applied Se compound. Increased thioredoxin reductase (TXNRD) activity and changes in mRNA expression levels of antioxidant proteins indicated the activation of cellular defense mechanisms. However, in txnrd-1 deletion mutants, no protective effects of the Se species were observed anymore, which was also reflected by differential gene expression data. CONCLUSION: Se species protect against chemically-induced reactive species formation. The identified immediate and sustained systemic effects of Se species give rise to speculations on possible benefits facing subsequent periods of inadequate Se intake.